2015
DOI: 10.5935/2238-3182.20150074
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients admitted for spinal cord injury in public teaching hospital

Abstract: The spinal cord injury (TRM) is an important cause of mortality in Brazil. The PRO/PET-Health III, a Federal Government program developed at the Federal University of Minas Gerais, sought to identify the profile of TRM victims assisted in a large general teaching hospital in Belo Horizonte. A cross-sectional, descriptive study, with analysis of electronic medical records of patients admitted for TRM, was conducted to determine its epidemiological profile. The results revealed the age, length of stay, type of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A study conducted in Minas Gerais, which evaluated hospitalized patients with SCI, found that the daily average of drug use was greater, approximately 10 [2]. One possible cause for this difference is that the subjects in the present study were outpatients, while the other were inpatients.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…A study conducted in Minas Gerais, which evaluated hospitalized patients with SCI, found that the daily average of drug use was greater, approximately 10 [2]. One possible cause for this difference is that the subjects in the present study were outpatients, while the other were inpatients.…”
Section: Discussionmentioning
confidence: 59%
“…One possible cause for this difference is that the subjects in the present study were outpatients, while the other were inpatients. Pharmacological therapy should be carefully monitored, since it involves risk of adverse reactions and longer hospital stay [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominance in this study of young male individuals with traumatic SCI is corroborated by a research study conducted in a large teaching hospital in the city of Belo Horizonte, state of Minas Gerais, Brazil, showing that all patients were male, with a mean age of 39 years old, which is consistent with the world and national incidence pattern of spinal cord trauma; the main etiology associated with the accident was trauma caused by firearms, which evidences the tendency of increased violence and criminality in large urban centers. 12 Another study showed that the trauma caused by firearm projectiles was responsible for 9.2% of the spinal cord injuries, with a mean of 14.8 new cases per year; 86.5% of them were male patients and 73.1% were under 30 years old. 13 Considering the strengths revealed in the process of adherence to rehabilitation of people with SCI and their families, welcoming is characterized by dedication in moments of care.…”
Section: Discussionmentioning
confidence: 99%